Survival of patients with non-small cell lung cancer in King Abdulaziz University Hospital, Jeddah, Saudi - Al Hajeili, Marwan R.; Alhejaili, Faris F.; Bakhsh, Salwa I. A.; Aljohaney, Ahmed A.; Iskanderani, Omar F.; Alsulami, Atheer F.; Alghamdi, Maha A.; Alghamdi, Wejdan A.; Banjar, Nujoud S. (International Journal Of Community Medicine And Public Health, 2019)
Background: The improvement in the survival rate from cancer is increased due to advancement in the early detection, combined modality therapy and right therapeutic strategies. This study was aimed to assess the survival outcomes of patients diagnosed with non-small cell lung cancer (NSCLC) at King Abdulaziz University Hospital (KAUH). Methods: This retrospective cohort study included all patients aged 14 years and older with a diagnosis of NSCLC from 2007 to 2017 using electronic medical records at KAUH. Data analysis was performed by using Stata SE, version 15.0. Survival was defined as the time the patient lived in months from the date of pathological diagnosis to the date of last follow-up or death. All variables in a univariate and multivariate analysis were included. Results: Adenocarcinoma was the most common type of NSCLC observed in both genders, accounting for 43.70% of all cases. Of the patients diagnosed with NSCLC the overall median survival was 12.2 months (interval=16.9). And among all variables, surgical treatment was associated with a 71% relative reduction in risk of death (hazard ratio 0.29, p<0.014), and chemotherapy a 57% relative reduction in risk of death (hazard ratio 0.43, p<0.013). Conclusions: The median age of diagnosis of NSCLC in Kingdom of Saudi Arabia (KSA) was younger than United States of America, this could be due to many factors including smoking. The number of lung cancer cases among women was lower than men.